Modeling paleogeographic scenarios of the last glacial cycle as a base for source-to-sink studies: An example from the northwestern shelf of the South China Sea. (November 2020) - Xiong, Ping; Dudzińska-Nowak, Joanna; Harff, Jan; Xie, Xinong; Zhang, Wenyan; Chen, Hongjun; Tao, Jiang; Chen, Hui; Miluch, Jakub; Feldens, Peter; Maciąg, Łukasz; Osadczuk, Andrzej; et al.
Graphical abstract: Highlights: DEM, seismic, and SL data are used for source-to-sink study of the SCS's shelf during LGC. SCS functioned as a changing oceanographic interface between the Pacific and Indic. Hainan Island served as main sediments source of Hainan delta during MIS4/3. SL change, Asian Monsoon and river migration are the main drivers. Abstract: Sea-level (SL) data from the Last Glacial Cycle (LGC) have been superimposed on to digital elevation models of the South China Sea (SCS) and adjacent areas, to generate regional paleogeographic scenarios related to 4th- to 5th-order Milankovitch climate cycles. These scenarios—at 123, 65, 60.5, 56, 20, and 0.5 kyr BP—showed that the SCS functioned as an oceanographic interface between the Pacific and Indian oceans during the LGC. A Late Pleistocene paleo-river delta (Hainan delta) offshore west of Hainan Island (China) was an important sediment routing system on the NW shelf of the SCS. To understand the origin of the Hainan delta better, paleo-reliefs of DEM56kyrBP and DEM65kyrBP were reconstructed, using seismic stratigraphy, sedimentology, and back-stripping methods. Geostatistical and geometric models of clinoforms and delta geometry, as well as the courses of the reconstructed paleo-distributary channels and paleo-river valleys, supported the interpretation that most delta sediment could be regarded as erosional products from Hainan Island. We hypothesized that an intensification of sediment supply outpaced SL rise during the Marine Isotopic Stages 4/3 transition, resulting in a normal regression during the formation of the Hainan delta. Morphodynamic modeling and meteorological data reanalysis further supported our interpretation that shifts in the Asian Monsoon system—combined with local meteorological effects on Hainan Island and with global SL changes—were the main drivers for the sediment source-to-sink systems at the NW SCS continental margin, during the LGC.